2016
DOI: 10.1002/ajcp.12029
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Binge Drinking in Adolescents through Implementation of the Strategic Prevention Framework

Abstract: The Strategic Prevention Framework (SPF) is a conceptual model that supports coalition-driven efforts to address underage drinking and related consequences. Although the SPF has been promoted by the U.S. Substance Abuse and Mental Health Services Administration’s Center for Substance Abuse Prevention and implemented in multiple U.S. states and territories, there is limited research on the SPF’s effectiveness on improving targeted outcomes and associated influencing factors. The present quasi-experimental study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…In particular, the CDC (2009) advocates for developing processes that facilitate student, family, and community engagement, as well as providing education and opportunities to enable families to be actively involved. Further, SAMHSA's strategic prevention framework proposes incorporating family, school, and community domains and focusing on policy and practice change via raising awareness (e.g., advertisements) and implementing alcohol compliance check guidelines which are promising in reducing underage alcohol use and binge drinking (Anderson-Carpenter, Watson-Thompson, Chaney, & Jones, 2016;Eddy et al, 2012). While this investigation did not assess specific components in which schools implemented AOD prevention/education, future research should seek to investigate the individual effects of exposure to different types of programming.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the CDC (2009) advocates for developing processes that facilitate student, family, and community engagement, as well as providing education and opportunities to enable families to be actively involved. Further, SAMHSA's strategic prevention framework proposes incorporating family, school, and community domains and focusing on policy and practice change via raising awareness (e.g., advertisements) and implementing alcohol compliance check guidelines which are promising in reducing underage alcohol use and binge drinking (Anderson-Carpenter, Watson-Thompson, Chaney, & Jones, 2016;Eddy et al, 2012). While this investigation did not assess specific components in which schools implemented AOD prevention/education, future research should seek to investigate the individual effects of exposure to different types of programming.…”
Section: Discussionmentioning
confidence: 99%
“…Seven quasi-experimental community coalition studies using nonrandomized designs to prevent adolescent AOD were included in our review (Anderson-Carpenter et al, 2016;Feinberg et al, 2007;Flewelling et al, 2005;Flewelling & Hanley, 2016), with three focused solely on process elements of program evaluations (Brown et al, 2015;Paine-Andrews et al, 1997;Yin et al, 1997). The quasi-experimental design studies reported varying descriptions of coalition activities and involved nonrandomized, community-level trials.…”
Section: Quasi-experimental Studiesmentioning
confidence: 99%
“…The quasi-experimental design studies reported varying descriptions of coalition activities and involved nonrandomized, community-level trials. All four studies employed individual-level assessments of youth risk behavior; however, Anderson-Carpenter et al (2016) also assessed community-level measures including enforcement of underage drinking laws.…”
Section: Quasi-experimental Studiesmentioning
confidence: 99%
“…Nowadays, a variety of interventions have been developed to tackle this public health issue (adolescent substance use) but those aimed at preventing BD speci cally are scarce [10][11][12]. Regard to alcohol use prevention in general, a meta-analysis carried out by MacArthur et al (2015) to investigate and quantify the effect of peer-led interventions to prevent tobacco, alcohol and/or drug use among young people concluded that such interventions may be effective, although the evidence base is limited overall and is characterized by small studies of low quality [13].…”
Section: Years Old) Inmentioning
confidence: 99%